2018
DOI: 10.1021/acs.est.8b00926
|View full text |Cite
|
Sign up to set email alerts
|

The Story of Ever Diminishing Vehicle Tailpipe Emissions as Observed in the Chicago, Illinois Area

Abstract: The University of Denver has collected on-road fuel specific vehicle emissions measurements in the Chicago area since 1989. This nearly 30 year record illustrates the large reductions in light-duty vehicle tailpipe emissions and the remarkable improvements in emissions control durability to maintain low emissions over increasing periods of time. Since 1989 fuel specific carbon monoxide (CO) emissions have been reduced by an order of magnitude and hydrocarbon (HC) emissions by more than a factor of 20. Nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…The fraction of light trucks (e.g., vans, sport-utility vehicles, pick-up trucks) in the passenger vehicle fleet have grown with time. 65 In SI Figure S6, we breakdown NO x (panel a) and CO (panel b) emission factors between passenger cars and light trucks, and by Tier 0−2 emission standards. We also show how emission factors from remote sensing data compare with MOVES.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The fraction of light trucks (e.g., vans, sport-utility vehicles, pick-up trucks) in the passenger vehicle fleet have grown with time. 65 In SI Figure S6, we breakdown NO x (panel a) and CO (panel b) emission factors between passenger cars and light trucks, and by Tier 0−2 emission standards. We also show how emission factors from remote sensing data compare with MOVES.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the late 1980s light and medium-duty vehicle emissions have experienced significant reductions across the U.S. despite average fleet age increases due to the effects of the 2008 recession and improved vehicle longevity (Bishop and Haugen, 2018;Bishop and Stedman 2014). This is in part the result of improved emissions control technology driven by more stringent standards and dramatic increases in their useful life.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies observed opposite NO emission trends due to the different fuel types concerned, i.e. gasoline and LPG vehicles in Bishop and Haugen (2018); Organ et al (2019) vs diesel vehicles in Huang et al (2018c); Pujadas et al (2017). RS studies showed that gasoline NOx reduced obviously in the past 15-20 years but diesel NOx did not reduce over the same period including those vehicles equipped with exhaust after-treatment systems for NOx control (Carslaw and Rhys-Tyler, 2013;Chen and Borken-Kleefeld, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…The on-road RS technology is a rapid, non-intrusive and economical tool for the monitoring and control of in-use vehicle emissions, which has gained significant attention recently. Bishop and Haugen (2018) analysed a large RS dataset collected in Chicago during 1989 to 2016. Sharp reductions of emission factors (g/kg fuel) of light-duty vehicles were observed, with CO reduced by one order of magnitude since 1989, HC by a factor of >20 since 1989 and NO by 79% since 1997.…”
Section: Introductionmentioning
confidence: 99%